Blockchain implementation in the food supply chain: a systematic literature review - Vu, Nam; Ghadge, Abhijeet; Bourlakis, Michael (University of Warwick, 2020)
This study explores the literature on the implementation of Blockchain in Food Supply Chain Management (FSCM) and attempts to disseminate key insights along with potential directions for future research. A systematic and rigorous process of searching and scanning resulted in 53 peer-reviewed papers for the review. Findings from the selected papers include drivers and barriers to the adoption of the technology, current applications of Blockchain, and typical structure of the system in FSCM. Suggestions for future researches include empirical works to examine Blockchain implementation at supply chain level and influential factors to the implementation process.
Keywords: blockchain; implementation; food supply chain